Emotional intelligence as predictor of learning performance in higher education: a SEM approach - Suson, Roberto; Duites, Adrian; Gamboa, Harlene Marie; Entice, Mae; Capuno, Jhon Froy; Cabaron, Achilles; Sim, Mary Jane; Paubsanon, Hermes (Frontiers in Education, 2025)
Emotional Intelligence (EI) is gaining recognition as an essential component of academic performance, especially in teacher education programs where emotional competence is critical for engaging with young learners. This research analyzes the significant impact of four emotional intelligence dimensions (Wong and Law Emotional Intelligence Scale) on Learning Performance among pre-service teachers in Bachelor of Early Childhood Education and Bachelor of Elementary Education programs in the Philippines. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to evaluate the measurement and structural models. The results showed that all four EI dimensions had a significant and positive effect on LP. ROE had a medium effect size, while the other three dimensions had small effect sizes. UOE was the strongest predictor of the path coefficient, which shows how important it is to leverage emotions to boost motivation and cognitive engagement. The model accounted for 57.6% of the variance in LP. These findings contribute to the literature by examining the relatively neglected environment of early childhood and elementary pre-service teachers, offering empirical evidence for the beneficial implications of several EI components in improving learning performance. The study provides theoretical implication for incorporating emotional intelligence development into teacher education programs to enhance academic performance and professional preparedness.